2011
DOI: 10.1186/1471-2458-11-442
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and lifestyle factors associated with overweight in a representative sample of 11-15 year olds in France: Results from the WHO-Collaborative Health Behaviour in School-aged Children (HBSC) cross-sectional study

Abstract: BackgroundThe prevalence of overweight in children and adolescents is high and overweight is associated with poor health outcomes over short- and long-term. Lifestyle factors can interact to influence overweight. Comprehensive studies linking overweight concomitantly with several demographic and potentially-modifiable lifestyle factors and health-risk behaviours are limited in adolescents - an age-group characterized by changes in lifestyle behaviours and high prevalence of overweight. Thus, the objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 57 publications
(172 reference statements)
11
55
2
4
Order By: Relevance
“…The established problems among the schoolchildren in Bulgaria are similar to those observed in recent decades in some of the European countries as well as in other countries worldwide as an increase in overweight among schoolchildren has been observed [15][16][17][18][19][20][21][22][23] . The outcomes resulting from the nationally representative survey in 1998 showed high incidence of overweight among schoolchildren, calculated according to the previous indices and criteria of WHO 2 from 1995, and reflecting a period of economic problems in Bulgaria 9 .…”
Section: Discussionsupporting
confidence: 59%
“…The established problems among the schoolchildren in Bulgaria are similar to those observed in recent decades in some of the European countries as well as in other countries worldwide as an increase in overweight among schoolchildren has been observed [15][16][17][18][19][20][21][22][23] . The outcomes resulting from the nationally representative survey in 1998 showed high incidence of overweight among schoolchildren, calculated according to the previous indices and criteria of WHO 2 from 1995, and reflecting a period of economic problems in Bulgaria 9 .…”
Section: Discussionsupporting
confidence: 59%
“…Regarding gender, as in this study, other studies have observed higher prevalence of breakfast skipping among girls [13,38,40]. One possible explanation for this relationship may be dissatisfaction with body image and the intention to lose weight due to media pressure and desire for thinness [32,41].…”
Section: Discussionsupporting
confidence: 54%
“…These differences might be explained in part by the criteria for classifying breakfast skipping. Some studies have assessed frequency groups of breakfast consumption [5,11,32,[35][36][37], while others are based on 24-hour recall [7,26], and still others classified as daily or not daily consumption [38,39], as in this study. This criterion was used because it had the best discriminatory power in this population, and because higher frequency of breakfast consumption is desirable, as it has protective effects, particularly against obesity [15,37].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 9 studies for screen time, 13 studies for TV viewing, and 1 study for total sedentary behaviour reported null findings. Within 19 studies, significant associations with body composition were not observed across all sex groups (Dupuy et al 2011;Hardy et al 2012;Ismailov and Leatherdale 2010;Jones et al 2010;Mejia et al 2013;Nigg et al 2011;Rey-Lopez et al 2012;Sigmundova et al 2014;Suglia et al 2013;Vaezghasemi et al 2012), ethnic groups (Saab et al 2011), age groups (de Jong et al 2013;Seo and Niu 2014;Zhang et al 2012), geographical locations (Taber et al 2012;Tambalis et al 2013), days of the week (Liou et al 2010), or measures of body composition (Kuriyan et al 2012;Sluyter et al 2013). Inconsistent findings were observed for doing homework and reading and primarily null findings were observed for accelerometer-derived sedentary time, breaks, and bouts as well as computer use, and video game use with body composition.…”
Section: Body Compositionmentioning
confidence: 95%